How the state legitimizes national development projects: The Third Development Axis case study, Slovenia - Goluža, Maruša; Šubic-Kovač, Maruška; Kos, Drago; Bole, David (Acta geographica Slovenica, 2021)
We analyzed planning mechanisms and evaluated their performance in achieving legitimacy in infrastructure planning in Slovenia. Planning mechanisms were divided according to the concept of input, throughput and output legitimacy. We conducted a document analysis and interviews to assess their effectiveness in achieving legitimate decisions. Although the analyzed decision-making process declaratively promoted democratic principles, the mechanisms failed to satisfactorily enhance the legitimacy of decisions. The study revealed inadequate communication approaches, both in the decision-makers’ relationship with the public and within the expert discourse. Accordingly, the study argues for more genuine communication with the public and within academia to address legitimacy challenges in increasingly conflictual decision-making processes.